Harga Minyak Dunia Terhadap Harga Emas Di Indonesia - Bima Pratama Putra; Alpon Satrianto (Universitas Negeri Padang, 2022)
This study aims to examine and analyze the effect of exchange rates, stock prices, and world oil prices on gold prices in Indonesia. The data in this study are time series data from 2004 to 2019. This type of research is descriptive, the data used is secondary data in the form of monthly data from 2004 to 2019 in Indonesia. In this study using ARDL (Autoregressive Distributed Lag) regression with Eviews 9. The test results (1) the gold price variable in the past from 2004 to 2019 had a positive and significant effect on gold prices in Indonesia; (2) the exchange rate variable from 2004 to 2019 showed positive and significant results; (3) on the other hand, stock prices and world oil prices show a negative but not significant relationship.